Why heterodoxy failed?: Analysis of the economic policy in the first stage of Alan García's government - Mujica, María Eugenia (1990)
This article analizes the first two years of Alan García's government -which correspond to the characteristics of an heterodox regime- on the light of a proposed model, based on the determination of aggregate demand and supply, and concentrated in the functioning of relative prices. It can be stated that economic success in the short term was followed by the appearance of inflationary pressures and the aggravation of unbalances in different sectors of the economy, as well as in relative prices. As a result, the economic program derived into a severe crisis by mid-1987.